Pemetaan Sosial Ekonomi Menuju Desa Iklim di Desa Pinggir Kabupaten Bengkalis Provinsi Riau - Widayat, Prama (Jurnal Indragiri Penelitian Multidisiplin, 2024)
Villages are the initial milestone for developing a country, if a village is strong it will have an impact on economic sustainability, for this reason it is necessary to map village potential so that later it can be developed and connected to environmental social responsibility (TJSL) programs. To build a village, potential data is needed, later this will become the basis for pentahelic collaboration to build villages. By looking at socio-economic aspects consisting of education level, employment, income, expenditure, waste management and the environment. The peripheral villages are dominated by oil palm plantations and the people also work as oil palm farmers. A small number work in the government, trade and private sectors. Other results are also in the agricultural sector, but very few people are involved in this field. The commodities produced include cassava and vegetables. They process the sweet potatoes into chips, tape, fried foods and others. The large area of plantation land should be supported by the availability of organic fertilizer but currently they only use manufactured chemical fertilizer. In the future, it is necessary to encourage the development of organic fertilizer production for the environmentally friendly fertilizer needs of the plantation and agricultural sectors.